Improving Students’ Writing Performance: A Self-regulated Strategy Development - Reski Pilu (Ethical Lingua: Journal of Language Teaching and Literature, 2014)
This research is Effective in teaching narrative writing to the students of the sixth semester of English students of English Study Program of Cokroaminoto Palopo University. This research aims to find out whether the use of POW + W = 2, H = 2 strategy efficacious to improve the students’ ability in writing of the sixth semester English department students of Cokroaminoto Palopo University. This research used a pre-experimental design. The population of this research was the sixth semester students of English department of Cokroaminoto University Palopo. The sample of this research was the sixth semester students where the total sample is 30 students. This research used cluster random sampling technique. The research data were collected by using instruments namely narrative text. Data on the students’ writing skill were analyzed by using descriptive and SPSS v.20 to find and analyzed the mean score, standar deviation and T-test. The results of the research that there is difference between pre-test and post-test, where the mean score of the pretest (74) is lower than the mean score of the post-test (86.58), It means that there is a significant improvement after treatment by using POW + WWW, W = 2, H = 2 as strategy in teaching short story writing. Therefore, The T-Test of the students’ writing in post-test was smaller than α (0.01 < 0.05), it can be concluded that using POW + WWW, W = 2, H = 2 is significance improving